Proposição de modelos de gamificação para sistemas de educação online: uma abordagem baseada na educação baseada em evidências - Nogueira Neto, Amaury (2016)
This work is the proposal to investigate the effects of specific elements of gamification, gamification addressing not only as a comprehensive concept, but trying to analyze the effectiveness of the use of the most used game mechanics in the context of education. By isolating specific game mechanics and use appropriate methods for evaluating their effectiveness in the classroom, we obtained a better understanding of how to create an ideal of gamification system that promotes and maintains the engagement and contribute positively to student learning. From conducting a controlled study, where the elements Point, Trophy and Ranking were analyzed, both in isolation as a combined way, could be seen that the use of such elements may show statistically significant contributions with regard to engagement from the students. In the face of findings, it sought to analyze how the results could contribute to the Information fields of study in Education and gamification, seeking information that subsidize the creation of the proposed model for their application in Mathematics discipline of teaching context for students high school in Brazil. The adoption of the proposed model can contribute to a greater engagement of students helping them in the core disciplines of high school.